Giving students effective written feedback - Burke, Deirdre; Pieterick, Jackie (New York : Mc Graw Hill., 2010)
This text is aimed at meeting the needs of tutors by examining professional and personal issues related to written feedback on student work.
include bibliographical references and index.
Keywords: College students -- Rating of -- Great Britain; Grading and marking (Students) -- Great Britain; Psychology